FAQ, teen life. (New York : Rosen Pub., 2011)
Provides information on topics that commonly concern teenagers, addressing personal finances, vaccines and vaccinations, plagiarism, social networking, gangs and urban violence, and cancer.
Cancer decisions for you and your family / Colleen Ryckert Cook -- Financial literacy / Mary-lane Kamberg -- Gangs and urban violence / Ann Byers -- Blagiarism / Liz Sonneborn -- Social networking / Colleen Ryckert Cook -- Vaccines and vaccinations / Christine Petersen.
Includes bibliographical references and indexes.
6.0
Young Adult
Young Adult
Keywords: Teenagers -- Juvenile literature; Teenagers -- Conduct of life -- Juvenile literature; Teenagers -- Health and hygiene -- Juvenile literature; Teenagers; Teenagers -- Conduct of life; Teenagers -- Health and hygiene; Teenagers; Teenagers -- Conduct of life; Teenagers -- Health and hygiene